Regulation of apoptosis in external auditory canal cholesteatoma by hepatocyte growth factor/scatter factor - Naim, Ramin; Shen, Ted; Riedel, Frank; Bran, Gregor M.; Sadick, Haneen; Hörmann, Karl (ORL, 2005)
Objectives: External auditory canal cholesteatomas (EACC) are characterized by focal invasion of squamous cell epithelium and accumulation of keratin debris in the apical part of the matrix. Apoptosis appears to be important in understanding the pathogenesis of EACC. Here the possible regulatory effect of the apoptosis mediated by hepatocyte growth factor (HGF)/scatter factor (SF)-c-Met-Fas in EACC is dicussed. Methods: We examined 17 EACC specimens for immunohistochemical expression of HGF/SF, c-Met, caspase 3 and Fas. The staining reaction was evaluated semiquantitatively. Results: HGF/SF was detected in mesenchymal tissue below the EACC epithelium. c-Met was expressed throughout the epithelium. Fas and caspase 3 were detected at increasing levels towards the apical layers of the EACC matrix. Conclusions: High levels of HGF/SF result in binding of HGF/SF to c-Met, releasing Fas to aggregate and bind to its death-inducing signaling complex. The result is apoptosis, marked by formation of dead squamous cells and sequestered keratin debris on the apical side of the cholesteatoma.